Development of a Fifteen-Minute City Index Using Walkability Scores and Age-Classified Population: The Case of Pasig City, Metro Manila, Philippines - Carlo Angelo R. Mañago; Marielle G. Nasalita; Cesar V. Saveron; Ynah Andrea D. Sunga; Alexis Richard C. Claridades (ISPRS International Journal of Geo-Information, 2025)
The 15-min city (FMC) is a people-oriented urban development strategy that aims to provide a higher quality of life by manifesting the people’s right to the city. This study proposes an FMC index that measures how close a specific area is to achieving the 15-min accessibility to the six social functions (living, working, supplying, caring, learning, and enjoying). In the case of Pasig City, social function service areas were generated in terms of walkability and walking speeds per age group. Grid-based and population-based FMCI were calculated based on the established weights of points of interest and social functions, as well as the barangay population distribution per age group. The results show that 90% of the barangays achieved an FMCI of 0.5 or higher. This study presents an in-depth yet replicable approach using open-source data, considering facilities in each social function based on necessity of each age group, as well as utilizing pedestrian walkability as an impedance. Further, high population-based FMCI barangays cluster in the southern-central part of the city. The developed FMCI offers a compelling rationale for other HUCs to assess urban planning strategies, such as zoning strategies in the context of the weighted importance of amenities, walkability, and population distribution.